Nurturing newborns in South Sudan series: Essential care for the small baby - Isaac Gawar; Grace J. Soma (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
"Nurturing newborns in South Sudan" is a series of clinical guidance reviews on newborn care for the South Sudan context. The first part of this series focused on essential care of the newborn giving standard recommendations for the birth, delivery and care of all newborns not in need of emergency lifesaving care immediately after birth.[1] Once out of danger, these newborns should receive the essential care package. The second part of this series reviews essential care for babies who are born 'small'. Babies who are born preterm (before 37 weeks gestation) and those with low birth weight (less than 2.5kg) fall under this category of 'small'.